Penggunaan Saluran Komunikasi Untuk Memenuhi Kebutuhan Informasi Wanita Pengusaha Kuliner Kota Depok - Diana Anggraeni; Mashadi Said; Diah Febrina (Jurnal Komunikasi Global, 2019)
The culinary business today is one of the most sought-after business alternatives in Depok. This can be seen that out of 1000 business actors in Depok in 2018, most of them are doing business in the culinary sector. Because the development of the culinary business is increasing rapidly, culinary entrepreneurs, especially women, need various information related to this business. This study aims to find out the communication channels used by women culinary entrepreneurs in Depok to meet their information needs. This study uses a quantitative approach with a survey method. The sample was chosen using a purposive sampling technique based on the characteristics of women who have culinary business, both online and offline. Data were collected by sending questionnaires online through a google form. Within two weeks, as many as 96 respondents were willing to fill out and return the questionnaire. The results of the study show that in the current technological development, the role of communication channels is crucial to support culinary business activities. Various types of culinary information are obtained very quickly when smart business actors utilize the right communication channels. The majority of women culinary entrepreneurs in Depok use communication channels through group chat and interpersonal communication channels, such as friends and family.